Evaluation of uric acid as a prognostic blood-based marker in a large cohort of pancreatic cancer patients. - Michael Stotz (Public Library of Science (PLoS), 2014)
Background Recently, chemical blood parameters gain more attraction as potential prognostic parameters in pancreatic cancer (PC). In the present study we investigated the prognostic relevance of the uric acid (UA) level in blood plasma at the time of diagnosis for overall survival (OS) in a large cohort of patients with PC. Patients and methods Data from 466 consecutive patients with ductal adenocarcinoma of the pancreas were evaluated retrospectively. Overall survival (OS) was analysed using the Kaplan-Meier method. To further evaluate the prognostic significance of the UA level, univariate and multivariate Cox regression models were calculated. Results None of the clinicopathological parameters (tumour grade, clinical stage, age, CA19-9 level, Karnofski Index (KI) or surgical resection) except gender was associated with UA level. In univariate analysis we observed the elevated UA level (<5.1 versus ≥5.1 mg/dl, p = 0.017) as poor prognostic factor for OS. In the multivariate analysis that included age, gender, tumour grade, tumour stage, surgical resection, CA19-9 level, the KI and UA level we confirmed the UA level as independent prognostic factor for OS (HR = 1.373%; CI = 1.077-1.751; p = 0.011). Conclusion In conclusion, we identified the UA level at time of diagnosis as an independent prognostic factor in PC patients. Our results indicate that the UA level might represent a novel and useful marker for patient stratification in PC management.